2013
DOI: 10.1002/hbm.22337
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and manipulation of somatosensory information in ventrolateral prefrontal cortex

Abstract: Neuroimaging studies of working memory (WM) suggest that prefrontal cortex may assist sustained maintenance, but also internal manipulation, of stimulus representations in lower-level areas. A different line of research in the somatosensory domain indicates that neuronal activity in ventrolateral prefrontal cortex (VLPFC) may also represent specific memory contents in itself, however leaving open to what extent top-down control on lower-level areas is exerted, or how internal manipulation processes are impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Neuroimaging studies suggest that the pre-frontal brain areas are involved in processes necessary for working memory (D’Esposito et al, 1999; Spitzer et al, 2014). A promising approach to assess working memory load in realistic environments is to measure brain activation of the operator with functional near-infrared spectroscopy (fNIRS).…”
Section: Introductionmentioning
confidence: 99%
“…Neuroimaging studies suggest that the pre-frontal brain areas are involved in processes necessary for working memory (D’Esposito et al, 1999; Spitzer et al, 2014). A promising approach to assess working memory load in realistic environments is to measure brain activation of the operator with functional near-infrared spectroscopy (fNIRS).…”
Section: Introductionmentioning
confidence: 99%
“…A recent effective connectivity study showed that rIFG modulates the excitatory influence between the pre-SMA and subthalamic nucleus (Rae, Hughes, Anderson, & Rowe, 2015). Consistent with the idea that response inhibition requires online maintenance of relevant information, rIFG has also been implicated in storing behaviorally relevant information in memory (Spitzer, Goltz, Wacker, Auksztulewicz, & Blankenburg, 2014;Marklund & Persson, 2012;Clark et al, 2007). More generally, tasks in which storage or maintenance of value or knowledge is required over several trials evoke associated activity in lateral PFC (Curtis & D'Esposito, 2003).…”
Section: Role Of Inferior Frontal Cortex In Processing Feedback In Acmentioning
confidence: 79%
“…Ventrolateral PFC receives converging input from the ventral visual stream, for example, information about the shape and color of stimuli (Takahashi, Ohki, & Kim, 2012;Sakagami & Pan, 2007), which it can then convert into templates for motor commands (Sakagami & Pan, 2007). Previous studies have shown that different regions in medial and lateral frontal cortex selectively interact with task-relevant and task-irrelevant brain areas to maintain sensory information needed for future decisions in memory (Spitzer et al, 2014;King et al, 2010;see Gazzaley & Nobre, 2012, for a review). The current finding opens up the question as to whether there is a dynamic interplay between frontal areas and occipital regions that relies on information from lower level processes of detailed visual stimuli features that are in themselves calling for response speed adaptations dependent on feedback or whether the interaction between reinforcement processes and cognitive control takes place higher up in the processing hierarchy.…”
Section: Sensory Input To Inferior Frontal Cortex and Its Relation Tomentioning
confidence: 99%
“…). The precentral gyrus has been implicated in sustained attention toward sensation, while the inferior frontal gyrus has been implicated in working memory for sensory processing . Thus, it is possible that performance on the vibration task may be mediated by memory and/or attention in individuals with progressive MS compared to those with relapsing‐remitting MS.…”
Section: Discussionmentioning
confidence: 99%
“…Although MaCRUISE output provides 49 gyral labels in each hemisphere, we a priori chose to examine only primary and secondary sensory areas. Thus, in addition to thalamic volume, we examined cortical thickness in primary and secondary cortical areas that have been shown to be related to sensory function: postcentral gyrus, precentral gyrus, superior parietal lobule, parietal operculum, supramarginal gyrus, inferior frontal gyrus (including pars opercularis, pars triagularis and pars orbitalis), middle frontal gyrus, and anterior cingulate gyrus . Differences among controls and individuals with MS and among relapsing and progressive subgroups were examined with Mann–Whitney tests.…”
Section: Methodsmentioning
confidence: 99%